2002
DOI: 10.1016/s0969-2126(02)00831-6
|View full text |Cite
|
Sign up to set email alerts
|

E. coli Dihydroorotate Dehydrogenase Reveals Structural and Functional Distinctions between Different Classes of Dihydroorotate Dehydrogenases

Abstract: The flavoenzymes dihydroorotate dehydrogenases (DHODs) catalyze the fourth and only redox step in the de novo biosynthesis of UMP. Enzymes belonging to class 2, according to their amino acid sequence, are characterized by having a serine residue as the catalytic base and a longer N terminus. The structure of class 2 E. coli DHOD, determined by MAD phasing, showed that the N-terminal extension forms a separate domain. The catalytic serine residue has an environment differing from the equivalent cysteine in clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
120
0
13

Year Published

2003
2003
2021
2021

Publication Types

Select...
2
2
2

Relationship

1
5

Authors

Journals

citations
Cited by 99 publications
(137 citation statements)
references
References 43 publications
4
120
0
13
Order By: Relevance
“…With the active site loop in the open conformation these direct interactions are not possible, but they occur via a water molecule and Ser-129 O␥ is instead hydrogen-bonded to Gln-138 O⑀1. From the comparison with the DHODB and DHODC structures, we have proposed that this serine and Gln-138 in DHODA act as hinges of the active site loop (17). The exchange of the Ser-129 with alanine leads to the loss of the hydrogen bond formed by the side chain and must affect the loop movement and orotate binding site.…”
Section: Crystal Structuresmentioning
confidence: 99%
See 4 more Smart Citations
“…With the active site loop in the open conformation these direct interactions are not possible, but they occur via a water molecule and Ser-129 O␥ is instead hydrogen-bonded to Gln-138 O⑀1. From the comparison with the DHODB and DHODC structures, we have proposed that this serine and Gln-138 in DHODA act as hinges of the active site loop (17). The exchange of the Ser-129 with alanine leads to the loss of the hydrogen bond formed by the side chain and must affect the loop movement and orotate binding site.…”
Section: Crystal Structuresmentioning
confidence: 99%
“…DHODA, DHODB, and DHODC (17) showed that Lys-213 only is conserved among the class 1a enzymes and that the open conformation seen in the K213E(Oro) structure corresponds to the conformation of the loop observed in the structure of the uncomplexed class 1B enzyme, DHODB (10). In the DHODB structure in complex with orotate the loop is in a closed conformation, but could only be traced partially, while in the open conformation it could be traced completely, indicating that it moves to carry out the reaction but is more stable in the open conformation.…”
Section: Roles Of Different Residues In Dhoda-mentioning
confidence: 99%
See 3 more Smart Citations